Communication and sport surveying the field - Billings, Andrew C.; Butterworth, Michael L.; Turman, Paul D. (SAGE, 2018)
This book examines a wide array of topics necessary to understand sports media, rhetoric, culture, and organizations from micro- to macro-level issues.